IDENTIFIKASI MODEL ARSITEKTUR JENIS POHON FAMILI LAURACEAE DI KAWASAN ARBORETUM SYLVA UNIVERSITAS TANUNGPURA PONTIANAK - Sitanggang, Evlin; Manurung, Togar Fernando; Rifanjani, Slamet (Universitas Tanjungpura, 2019)
The tree architecture model is one of the important morphological features of the plants in characterizing each tree. Trees are plants with woody stems, deep roots, and have branches far from the ground and are more than 3 meters high (Hakim and Utomo 2003). trees are also one of the soft elements (softcape) that are very often used in the development of a site or landscape with a variety of unique characteristics. One of the unique characteristics of a tree is the dominant form of tree architecture formed by its canopy. This research was carried out at the Sylva Arboretum in Tanjungpura Pontianak for 3 weeks starting from July 4 2018 to July 24 2018 to observe and identify the architectural model of the lauraceae family tree. The research objective was to determine the architectural model of the Lauraceae family tree in Sylva Arboretum in Tanjungpura University Pontianak. The research method used is the exploration method, which is done by roaming, which means that observations can be made with visual and physical contact. Based on the results of the research and discussion, lauraceae family tree architecture models found in the Arboretum Sylva Area of Tanjungpura University Pontianak as many as four architectural models namely Rauh, Roux, Petit and Scarrone. The four architectural models were found in six species of trees, namely Ulin (Eusideroxylon zwageri), Medang sahung (Achiodaphne glabra), Medang pasir (Litsea eliptica), Medang bubur (Litsea resinosa), Medang sisik (Dehaasia firma), and Kayu manis (Cinnamomum iners).Keyword: Family of Lauraceae, Model of Tree Architecture, Sylva Arboretum